2000
DOI: 10.1121/1.429590
|View full text |Cite
|
Sign up to set email alerts
|

The Huygens entrainment phenomenon and thermoacoustic engines

Abstract: The earliest known reference to the mode-locking, or entrainment, of two maintained oscillators is Christiaan Huygens' description of two pendulum clocks "falling into synchrony" when hung on the same wall. We describe an analogous phenomenon in acoustics-the mode-locking of two thermoacoustic engines which have their cases rigidly welded together, but which are otherwise uncoupled. This "mass-coupling" might compete with acoustic coupling when the latter is used to enforce antiphase mode-locking in such engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 6 publications
0
14
1
Order By: Relevance
“…On the contrary, in their study of TA engine arrays McDonald and Symko [27] found the engines in a two-engine array entrained at a common frequency with approximately zero phase difference. The present result is also different from the TA engine pair studied by Spoor and Swift [29,30] for which the two engine outlets were connected through a half-wavelength tube. If vibration was completely cancelled in the coupled TA engines they studied, the half-wavelength tube must yield a 1801 phase difference between the two engines.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in their study of TA engine arrays McDonald and Symko [27] found the engines in a two-engine array entrained at a common frequency with approximately zero phase difference. The present result is also different from the TA engine pair studied by Spoor and Swift [29,30] for which the two engine outlets were connected through a half-wavelength tube. If vibration was completely cancelled in the coupled TA engines they studied, the half-wavelength tube must yield a 1801 phase difference between the two engines.…”
Section: Resultscontrasting
confidence: 99%
“…The Huygens mode-locking phenomenon [30] predicts two or more self-maintained oscillators would lock in frequency and phase. In the present investigation of TA laser pairs, the frequencies of the TA lasers were determined primarily by the lengths of the glass tubes, and the phase difference between the two laser outputs was never locked when the laser openings were far apart.…”
Section: Resultsmentioning
confidence: 99%
“…Entrainment refers to a process whereby two nearby oscillating systems, such as clocks, having similar periods, fall into synchrony (Huygens, 1666 as cited by Spoor and Swift, 2000). Many synchronization phenomena in motor movements, including those of speech, have been likened to this process (Haken et al, 1985;Kelso et al, 1986).…”
Section: Entrainmentmentioning
confidence: 96%
“…Some studies have focused on the description of the variety of nonlinear dynamics behavior observed in experiments (synchronization [24,25], route to chaos [26],...). Other studies [27,28,29,30,31] have focused on the forcing of acoustic oscillations in the context of thermoacoustic engines. In particular, a proof-of-concept study provided by Desjouy et al [28] in an annular engine has demonstrated that the addition of two auxiliary sources, appropriately tuned, can significantly improve the overall efficiency.…”
Section: Introductionmentioning
confidence: 99%